Annika desnuda - Álvarez Gil, Antonio, 1947- (Madrid : Editorial Verbum, 2015)
A young male Cuban painter takes up residence in Stockholm. His life is complicated by all the necessities of fitting into a new culture, his turbulent relationship with Annika, a Swedish woman, and an entanglement with the "Collar of the Four Caves of the Mountain", once stolen by Pizarro from the last king of the Incas.
Online resource; title from PDF title page (Digitalia, viewed September 27, 2016)
Keywords: Cubans -- Sweden -- Stockholm -- Fiction; Painters -- Sweden -- Stockholm -- Fiction; Man-woman relationships -- Fiction; Electronic books